2015
DOI: 10.3109/15513815.2015.1087610
|View full text |Cite
|
Sign up to set email alerts
|

Do Placental Histopathologic Characteristics Differ with Gestational Ages in Preterm and Term Deliveries?

Abstract: The study aim is to evaluate the placental histopathological characteristics and maternal risk factors in preterm and term births according to their weeks of gestation. We designed a prospective study involving a patient population (n = 355) composed of pregnant women who delivered preterm (n = 216) and term neonates (n = 139). The preterm births were divided into three groups as extremely (n = 22), moderate (n = 96) and late preterm (n = 98) births. The statistical analyses were performed using SPSS version 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…5,6 There is a large body of evidence that a cascade of activations of cellular components and mediators of inflammatory pathways results in onset of extremely preterm and very preterm births. [13][14][15] The current study confirms that extremely preterm and very preterm births are associated with a high incidence of chorioamnionitis, deciduitis and funisitis that represents infection-related placental and umbilical cord lesions. Most cases of histopathological chorioamnionitis represent subclinical infection.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…5,6 There is a large body of evidence that a cascade of activations of cellular components and mediators of inflammatory pathways results in onset of extremely preterm and very preterm births. [13][14][15] The current study confirms that extremely preterm and very preterm births are associated with a high incidence of chorioamnionitis, deciduitis and funisitis that represents infection-related placental and umbilical cord lesions. Most cases of histopathological chorioamnionitis represent subclinical infection.…”
Section: Discussionsupporting
confidence: 72%
“…13 Potentially, infection may develop early in gestation, before membrane fusion of the chorioamnion of the gestational sac to the opposite uterine wall at 19 -20 weeks, and then later after fusion, transmitted to the conceptus. [13][14][15] In the literature, it is found that 40 % of idiopathic preterm births placentas have chronic deciduitis. [13][14][15] Further clinical and pathological studies may improve the understanding of the implications of this entity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations